2016
DOI: 10.4103/2277-9175.187398
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of shock wave therapy and Laser therapy effect in elimination of symptoms among patients with myofascial pain syndrome in upper trapezius

Abstract: Background:The aim of this study is to compare the effects of laser therapy and shock wave therapy for symptoms treatment among patients with MPS in the upper trapezius muscle.Materials and Methods:In a clinical trial study, 46 patients were selected based on the clinical criteria and physiathrist diagnosis. Subjects were randomized into two groups as follows: Twenty individuals were assigned to exercise-medication-laser therapy group, and 26 to exercise-medication-shock wave therapy group. The pain was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The characteristics of the included studies are shown in Supplementary Appendix 2 (Supplemental Digital Content 3, http://links.lww.com/PHM/C68). Of the 27 RCTs included, 12 compared ESWT against a control ESWT, [17][18][19][20][21][22][23][24][25][26][27][28] and 18 compared ESWT, [17][18][19][20][21][22]26,[29][30][31][32][33][34][35][36][37][38][39] with other interventions. Most of the trials included two arms, except for six trials, which were three-armed studies.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included studies are shown in Supplementary Appendix 2 (Supplemental Digital Content 3, http://links.lww.com/PHM/C68). Of the 27 RCTs included, 12 compared ESWT against a control ESWT, [17][18][19][20][21][22][23][24][25][26][27][28] and 18 compared ESWT, [17][18][19][20][21][22]26,[29][30][31][32][33][34][35][36][37][38][39] with other interventions. Most of the trials included two arms, except for six trials, which were three-armed studies.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
“…In terms of the participants' gender, 802 (69.49%) were women; of note, six trials did not report this information. [19][20][21][32][33][34] Their ages ranged between 18 and 70 yrs; see Supplementary Appendix 2 (Supplemental Digital Content 3, http://links.lww.com/ PHM/C68). In terms of the treated area, 22 studies were carried out on patients with cervical and shoulder complaints, three studies were conducted on the leg/foot region, 25,27,28 and two trials were conducted on the lumbar spine region.…”
Section: Qualitative Summary Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They started to stretch the muscle slowly and gradually with contralateral neck side flexion and ipsilateral neck rotation for 30 sec and relaxed afterward for 30 sec. The 30-sec intervals were repeated three times consecutively and three times during a day (39).…”
Section: Interventionmentioning
confidence: 99%
“…Trigger point might be implemented in every muscle or muscular group, but they are often observed in muscles under vigorous stress, or the muscles do not undergo full periods of contraction and relaxation. The trapezius, levator scapula, and infraspinatus muscles are involved in the upper body ( 3 ). However, the above symptoms, such as those seen in fibromyalgia, are associated with sleep disturbances, and in fact, myofascial pain syndrome and fibromyalgia are two ends of the disease spectrum ( 4 ).…”
Section: Introductionmentioning
confidence: 99%